Higher Order Thinking Skill of Students Assisted by Mathematics Olympiad Senior High School in Solving Algebra Problems in Terms of Self Regulated Learning - Hidayatulloh, Muhammad Syarif; Oktavianingtyas, Ervin; Murtikusuma, Randi Pratama; Susanto; Putri, Inge Wiliandani Setya (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2024)
This study aims to describe the higher-order thinking skills of students assisted by the Mathematics Olympiad of SMA Negeri 2 Jember in solving algebra problems in terms of self-regulated learning. This research is included in qualitative description research. Data were obtained from the results of self-regulated learning questionnaires, written tests/higher-order thinking skills tests, and interviews. Self-regulated learning questionnaire data aims to group students in low, medium, and high categories. In this study there were 5 research subjects where 4 students with high self-regulated learning ability and 1 student with moderate self-regulated learning ability. Test and interview result data are used to describe the higher-order thinking skills of students assisted by the Mathematics Olympiad in solving algebraic problems. The results showed that, students with high self-regulated learning ability met all indicators of higher-order thinking skills, students with self-regulated learning ability were meeting until the evaluation stage. Students with low self-regulated learning skills were not found in the subjects of this study.